(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Proverbs are among the most enduring forms of verbal folklore, encapsulating centuries of human experience and cultural values in brief, memorable expressions. In both English and Uzbek traditions, proverbs involving medical lexicon provide insights into the folk understanding of illness, treatment, and the healer’s role. This article offers a comparative and thematic analysis of such proverbs to explore how folk medicine and cultural attitudes toward health are encoded in language. The findings show that while English proverbs emphasize individual responsibility and rational health practices, Uzbek proverbs highlight patience, spiritual well-being, and communal trust in healers. This contrast reflects broader epistemological and cultural differences between the Western and Eastern approaches to medicine.